Is Matter the Same as Its Potency? Some Fourteenth-Century Answers - Friedman, Russell L. (Vivarium, 2021)
Abstract Is prime matter the same as its potency ( potentia ), its readiness to take on the entire gamut of corporeal substantial forms? This question, arising from a passage in Averroes, lies at the core of later medieval hylomorphism and was hotly debated. The present article looks at three answers to the question by figures from the first half of the fourteenth century: Gerald Ot who takes a Scotistic approach to the issue, John of Jandun and Peter Auriol taking an Averroan tack, and John Buridan with a nominalistic outlook. The discussion reveals a diversity of positions on the nature of potency and its relation to actuality, and in the case of Buridan an unusual view at the heart of his matter theory: the direct inherence of accidental forms in prime matter.